The Influence of Entrepreneurial Orientation and Skills on Small Business Performance - yadewani, DORRIS YADEWANI (ADPEBI, 2022)
The purpose of this study is to investigate the impact of entrepreneurial orientation on the performance of small and medium-sized enterprises (SMEs) in Padang City, and the impact of skills on SME performance. The participants in the study were mostly business owners in Padang. Most of them said that they were very satisfied with the city's infrastructure. The sampling technique was purposive, specifically targeting specific items. There are 75 samples in total. The author employs a linear regression method using hypothesis testing with SPSS software version 22. The results of this study suggest that having orientation and entrepreneurial skills is a key factor in the success of small businesses.